Statistical optimisation of growth conditions and diesel degradation by the Antarctic bacterium, Rhodococcus sp. strain AQ5‒07 - Ahmad Roslee, Ahmad Fareez; Zakaria, Nur Nadhirah; Convey, Peter; Zulkharnain, Azham; Lee, Gillian Li Yin; Claudio, Gomez-Fuentes; Ahmad, Siti Aqlima (Springer, 2020)
Petroleum pollution is a major concern in Antarctica due to the persistent nature of its hydrocarbon components coupled with the region’s extreme environmental conditions, which means that bioremediation approaches are largely inapplicable at present. The current study assessed the ability of the psychrotolerant phenol-degrader, Rhodococcus sp. strain AQ5-07, to assimilate diesel fuel as the sole carbon source. Factors expected to influence the efficiency of diesel degradation, including the initial hydrocarbon concentration, nitrogen source concentration and type, temperature, pH and salinity were studied. Strain AQ5-07 displayed optimal cell growth and biodegradation activity at 1% v/v initial diesel concentration, 1 g/L NH4Cl concentration, pH 7 and 1% NaCl during one-factor-at-a-time (OFAT) analyses. Strain AQ5-07 was psychrotolerant based on its optimum growth temperature being near 20 °C. In conventionally optimised media, strain AQ5-07 showed total petroleum hydrocarbons (TPH) mineralisation of 75.83%. However, the optimised condition for TPH mineralisation predicted through statistical response surface methodology (RSM) enhanced the reduction to 90.39% within a 2 days incubation. Our preliminary data support strain AQ5-07 being a potential candidate for real-field soil bioremediation by specifically adopting sludge-phase bioreactor system in chronically cold environments such as Antarctica. The study also confirmed the utility of RSM in medium optimisation.